Control of Vector-Borne Human Parasitic Diseases - F, Genta (2016)
Vector-borne diseases (VBD) transmitted by arthropods are responsible for over 1 billion cases and 1 million deaths every year, corresponding to at least 17% of all infectious diseases in human populations [1]. Among them, we can find malaria, leishmaniasis, onchocerciasis, lymphatic filariasis, Chagas disease, and African trypanosomiases, as well as several arboviral diseases (arthropod-borne virus) such as dengue and Zika virus. Some of these have reemerged in new parts of the world and have become a topic of growing importance in public health and in political and scientific agendas [2]. Several factors are contributing towards the reemergence of VBDs. On the one hand, the spread of resistance to drugs in pathogens has become a major obstacle for the effective treatment of some VBDs [3], and the emergence of new strains of arboviruses (e.g., Zika virus in Brazil) has created new challenges for health care systems [4]. On the other hand, an increase in insecticide resistance is threatening the sustainability of vector control programmes in several tropical regions [5]. Additionally, the expansion of different vector populations due to climate change is becoming a growing concern in temperate countries, where vector control programs have been discontinuous for almost 50 years [6, 7]. The scientific community has been trying to overcome these challenges by creating new strategies and tools to improve the diagnosis and treatment of VBDs and by developing new methodologies and targets for vector control campaigns. This special issue of BioMed Research International compiles nine topical articles that explore recent advances in research of an eclectic range of pathogens, vectors, and human diseases affecting several regions of the world.